Testing Multi-Theory Model (MTM) in Predicting Physical Activity Behavior Among Upper Elementary School Children in Northern India - Poonam KHANNA; Tejinder Pal SINGH; Tarundeep SINGH; Rekha KAUSHIK; Manoj SHARMA (Journal of Health and Social Sciences)
Introduction: Physical inactivity in children is a precursor to childhood obesity, which is a major public health concern due to its increasing prevalence over the years. Aim of this study was to predict physical acti- vity (PA) behavior among upper elementary school children from Northern India through Multi -Theory Model (MTM). Methods: The Multi-Theory Model (MTM) was used to predict PA behavior among 214 upper elementary school children in District Ambala, Haryana, India. A 38-item Physical Activity (PA) questionnaire was used to assess the constructs of MTM. Significant predictors of PA behaviour change (i.e., initiation and sustenance) were assessed by using stepwise multiple regression. Results: Our findings showed that the mean for the intention to initiate engaging in 60 minutes of physical activity every day in the upcoming week was 2.14 units (SD = 1.23, possible range 0-4 units). The initiation model explained 12.5% variance in the intention to start PA behavior change. Sustenance model explained 5.3% of the variance in the intention for the sustenance of 60 minutes of PA every day. Examining the su- stenance model, two constructs of emotional transformation (β = 0.169, P = 0.012) and practice for change (β = 0.177, P = 0.008) were significant predictors. Discussion and Conclusion: In conclusion, MTM is a useful framework to design interventions to pro- mote physical activity among upper elementary school children in India. More empirical work needs to be undertaken in India, using randomized controlled trials that operationalize expanded form of this model.